1
$\begingroup$

I am trying to implicitly differentiate the following function: $$ \lambda = \exp \left[ \left( \alpha + \frac{s}{\lambda-s} \right)^{-1} \right] $$ Can someone help me with this?

$\endgroup$
  • $\begingroup$ Mathematica gives me $\dfrac{\mathrm d\lambda}{\mathrm d\alpha} = \dfrac{(s-\lambda )^2}{s-\exp[-(\alpha +s/(\lambda -s))^{-1}] (\alpha (\lambda - s)+s)^2}$. $\endgroup$ – user856 Jul 6 '15 at 19:45
0
$\begingroup$

Before making the differentiation you may simplify the equation such as

$$\ln(\lambda)=-\bigg(\alpha+\frac{s}{\lambda-s}\bigg)$$ $$\ln(\lambda)=-\bigg(\frac{\alpha(\lambda-s)+ s}{\lambda-s}\bigg)$$ $$(s-\lambda )\ln(\lambda)=\alpha(\lambda-s)+ s$$

Now you can differentiate as below

$$-\ln(\lambda)d\lambda+\frac{s-\lambda }{\lambda}d\lambda=(\lambda-s)d\alpha+\alpha d\lambda$$ $$\bigg(\alpha+\frac{s-\lambda }{\lambda}-\ln(\lambda)\bigg)d\lambda=(\lambda-s)d\alpha$$ $$\rightarrow \frac{d\lambda}{d\alpha}=\frac{(\lambda-s)}{\alpha+\frac{s-\lambda }{\lambda}-\ln(\lambda)}$$

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.